Strategic foresight for the post-2015 development agenda (UN New YorkUS, 2015)
Identifies, analyses and presents for discussions, key issues concerning the role of strategic foresight for policymakers, particularly in development countries.
Keywords: TECHNOLOGY ASSESSMENT